(untitled) (Ozone Therapy Global Journal, 2012)
Ozonethe rapy is on the agenda and figures at test to its growing importance. The ozonetherapy is increasingly practiced in different parts of the world. The existence of more than 40 national and international associations of ozonetherapy and more than 26 000 ozonetherapists confirm it. However, while ozone was discovered in 1785 by Dutch physicist Martin van Marum (1750-1837) and had been synthesized in May 1840 by the German chemist Christian Friedrich Schönbein (1799-1868), history has shown that it has been difficult to have a significant presence in the world’s medical agendas. Only Russia, Cuba, Spain and Italy have provisions from the authorities that specify the criteria to be met so that they can practice. These provisions are analyzed in this study, to rule in favor of working for the regularization of ozonetherapy, with reference to the measu res taken by the se countries. Specific points are proposed and a methodology that should be taken into account when developing a strategy that can lead to the regularization of ozonetherapy in countries where it is still widely practiced